Tools for Soil Organic Carbon Estimation and Management - UNCCD Science-Policy Interface (United Nations Convention to Combat Desertification, 2019)
Land degradation neutrality (LDN) is achieved if land degradation is avoided or reduced, and new degradation is balanced by reversing degradation elsewhere in the same land type through restoration or rehabilitation. The primary instrument for avoiding and reducing degradation is the application of sustainable land management (SLM) approaches and technologies. Because of its multifunctional roles and its sensitivity to land management, soil organic carbon (SOC) is one of the three global indicators for LDN, so predicting and monitoring change in SOC is vital to achieving LDN targets. Measuring SOC is challenging because SOC stock is highly variable across landscapes, even within the same soil type and land use, and SOC stock fluctuates over time. Predicting the potential change in SOC stock due to changes in land management is also a challenge. Accurate evaluation of SOC stock change resulting SCIENCE-POLICY BRIEF Tools for Soil Organic Carbon Estimation and Management from SLM interventions is often limited by the availability of data and the performance of tools/models for SOC assessment. Therefore, targeted investment in SOC estimation is vital. Guidance on harmonized methods that provide accurate estimations of changes in SOC stocks resulting from SLM interventions is required. Software tools and biophysical models for SOC assessment can help “fill the gaps” in measured datasets for SOC estimation. The following decision trees will guide efforts to predict change in SOC under alternative SLM practices, and monitor SOC change in response to SLM interventions, and thereby support decision-makers to pursue the right SLM interventions in the right locations, at the right time, at the right scale with the overall goal to increase or maintain SOC and improve soil health in support of LDN achievement.